Research on therapeutic clinical trials including immunotherapy in triple-negative breast cancer: a bibliometric analysis - Qi Xu; Xiaoyu Feng; Siyuan Qin; Yu Hong; Rui Cui; Jia Liang; Zhuya Xiao; Yuan Li (Frontiers in Oncology)
BackgroundBreast cancer, particularly triple-negative (TNBC), is a leading malignancy with aggressive traits and high metastasis rates. Clinical trial is an important tool for optimizing therapeutic strategies in the evaluation of the safety and efficacy for TNBC. Our bibliometric study of TNBC clinical trials aims to assess therapeutic strategies, identify trends, and explore advancements in treatment. We focus on mapping knowledge development, including key research entities and topics, and analyzing research trends and emerging methods. This analysis intends to inform future research, especially in personalized and precision medicine for TNBC.MethodsWe selected publications on clinical trials for the treatment of TNBC from 1997 to 2024 in the Web of Science Core Collection (WoSCC). After an initial screening, we downloaded key data including titles, publication years, authors, countries, institutional affiliations, journals, keywords, and abstracts, and saved them in BibTex format. We then conducted a bibliometric analysis using Bibliometrix in R and VOSviewer to illustrate the prospects, highlights, and trends of TNBC treatment options. Furthermore, to emphasize the hot topics in TNBC treatment strategies, we performed a bibliometric analysis of immunotherapy using the same approach.Results1907 publications were included, most of which were from China, Italy, and the United States. The number of annual publications has increased dramatically since 2010. The focus of TNBC clinical trial research has shifted from understanding the biology, such as breast cancer subtyping and genotyping, to novel therapeutic approaches. The major advancement in clinical trials is the switch from late-stage palliative treatment to early preoperative neoadjuvant therapy, as more TNBC cases are discovered at an early stage. Immunotherapy is also highlighted with additional alternatives for advanced or metastasized TNBC, such as targeted inhibitors with unusual mutation rates and antibody drug conjugates (ADC).ConclusionsThis investigation made it apparent how immunotherapy has recently made major advancements in TNBC treatment plans and how ADCs, or targeted therapies, are currently popular for TNBC. By identifying significant papers, comprehending trending topics, and collaborating across multiple disciplines, this study may accelerate research on TNBC therapy options.